PNB dan Pengurusan Hotel Patuh Syariah - Nor ‘Azzah Kamri; Suhaili Sarif; Nor Aini Ali; Nor AzizahTukiran (USIM Press, 2024)
Vol. 31 (2020): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences [August 2020]